The use of doxorubicine at low doses for elevation of LAK-activity toward explants and cells of MC-rhabdomyosarcoma and В16 melanoma resistant to doxorubicin - Berezhnaya, N.M.; Vinnichuk, Yu.D.; Belova, O.B. (Experimental Oncology, 2008)
Aim: To study the influence of doxorubicin at low doses on antitumor action of activated (LAK) and non-activated lymphocytes from lymph nodes toward tumor cells of mice bearing doxorubicin-resistant and doxorubicin-sensitive transplantable MC-rhabdomyosarcoma and B16 melanoma. Materials and Methods: The study was carried out on BALB/c mice bearing MC-rhabdomyosarcoma and С57BL/6 mice bearing В16 melanoma. Explants, tumor cells and lymphocytes were cultivated in diffusion chambers, filters were stained with hematoxylin by Karachi, and morphology of preparations was examined. Results: At the day 7 of tumor growth in mice bearing resistant MC-rhabdomyosarcoma, non-activated lymphocytes pretreated with low-dose doxorubicin possess the highest antitumor activity, and in mice bearing doxorubicin-resistant B16 melanoma the highest antitumor activity was detected for lymphocytes after combined cultivation with IL-2 and doxorubicin. At the day 14 of tumor growth, LAK obtained from lymphocytes pretreated with doxorubicin possess the highest cytotoxic activity toward resistant tumor cells both of MC-rhabdomyosarcoma and B16 melanoma. There was no such effect in the case of sensitive tumors. Conclusion: To elevate antitumor activity of LAK toward MC-rhabdomyosarcoma and B16 melanoma cells, low doses of doxorubicin could be used at certain conditions of LAK generation. Цель: изучить влияние малых доз доксорубицина на противоопухолевое действие активированных (ЛАК) и неактивированных
лимфоцитов лимфатических узлов по отношению к опухолевым клеткам мышей с резистентными и чувствительными к
доксорубицину перевивной МХ-рабдомиосаркомой и меланомой В16. Материалы и методы: исследования проведены на
мышах линии BALB/c с МХ-рабдомиосаркомой и С57BL/6 c меланомой В16. Эксплантаты, опухолевые клетки и лимфоциты
культивировали в диффузионных камерах и окраской фильтров гематоксилином по Караччи. Исследовали морфологическую
картину полученных препаратов с учетом критериев роста опухоли. Результаты: сопоставление результатов противоопухолевой
активности активированных и неактивированных лимфоцитов, полученных в различных условиях, показало следующее.
На 7-е сутки у мышей з резистентной МХ-рабдомиосаркомой наибольшей противоопухолевой активностью обладали
неактивированные лимфоциты, предварительно обработанные малыми дозами докорубицина, а у мышей з резистентной
меланомой В16 — лимфоциты после сочетанного культивирования с ИЛ-2 и доксорубицином. На 14-е сутки роста опухоли
наибольшей цитотоксической активностью обладали ЛАК, полученные из лимфоцитов, предварительно обработанных
доксорубицином, в отношении резистентных опухолевых клеток как перевивной МХ-рабдомиосаркомы, так и меланомы В16.
Относительно чувствительных клеток указанных опухолей такой эффект не отмечался. Выводы: для усиления противоопухолевой
активности ЛАК по отношению к клеткам МХ-рабдомиосаркомы и меланомы В16, резистентных к доксорубицину, могут быть
использованы малые дозы доксорубицина при соблюдении определенных условий получения ЛАК.